The Teacher Professionalism: Qualifications Contribute to be a Professional Teacher - Marleni Marleni (Universitas PGRI Palembang, 2018)
Abstract Qualifications and certifications are needed to be considered for professional teachers. Hence new initiatives (policy) are regularly taken to further strengthen the professionalism of teachers. These initiatives are chiefly directed to the profession – the status, respect, and much less to the inside of teaching process – the attitudes and actions of individual teachers in their daily teaching practice. The pedagogical and didactic theories should be put together for professional development in promoting learning in the classroom. This paper aims to systematically find out the qualifications required essentialy by teachers to successfully perform their pedagogical and didactic duties competently and professionally; what makes up their personal professionalism. The paper also will try to verify the conclusions reached in related literature regarding a holistic approach to make up the profile of a “good teacher” and hopefuly it can contribute to a systematic and analytical description of professional knowledge required for the successful performance of a profesional teacher.Keywords: qualifications, professional, teachers